Antimicrobial susceptibility test of pathogens isolated from urinary tract infection suspected cases - Yadav, K; Prakash, S; Serayi, RC; Shilpkar, T; Shrestha, S (Janaki Medical College Journal of Medical Science, 2014)
Background and objectives: Urinary tract infection (UTI) is associated with multiplication of organisms in urinary tract and is defined by the presence of more than 105 organisms per ml in a midstream sample of urine (MSU). UTI is most commonly acquired bacterial infection in ambulatory and hospitalized populations. E.coli is the most predominant organism to colonise the urethral meatus and perineum before ascending to the bladder. Drug resistance of pathogens is a serious medical problem, because of very fast arise and spread of mutant strains that are insusceptible to medical treatment of UTI. Therefore, this study was carried out to determine the common pathogenic bacteria causing UTI and to determine their antibiotic susceptibility pattern. Material and Methods: Mid stream urine samples of the UTI suspected pateints were collected in the Mid Stream Urine (MSU) samples were collected in the sterile clean dry wide mouthed bottle. Standard protocol was followed to isolate and identify organism which was followed by disc diffusion antibiotic sensitivity tests. Results: A total of 100 samples were collected. Out of 100 samples, 25 samples showed a significant growth E.coli, Citrobacter diversus, Klebsiella pneumoniae, Staphylococcus aureus were isolated. E.coli (84%) was found to be the most prevalent causing UTI. Conclusion: UTI was found more common in female than male and E.coli was found to be main causes of UTI. Ciprofloxacin showed more effective drugs in the treatment of UTI. DOI: http://dx.doi.org/10.3126/jmcjms.v2i1.11393 Janaki Medical College Journal of Medical Sciences (2014) Vol. 2 (1): 28-34